If x= secθ-cosθ,y=secⁿθ-cosⁿθ,then......,Select Proper option from the given options.
(a) (x²+4)(dy/dx)²=n²(y²+4)
(b) (x²-4)(dy/dx)²=n²(y²-4)
(c) (x²+4)(dy/dx)²=1
(d) (x²+4)(dy/dx)²=y²+4
Answers
Answered by
0
Hello,
Answer: (a) (x²+4)(dy/dx)²=n²(y²+4)
Solution:
x= secθ-cosθ
dx/dθ = secθ tanθ - (-sin θ)
dx/dθ = secθ tanθ +sin θ
dx/dθ = tanθ (secθ + cos θ) ---eq1
same way differentiate y =secⁿθ-cosⁿθ
dy/dθ = n sec(ⁿ-1)θ secθ tanθ - n cos(ⁿ-1)θ(-sinθ)
dy/dθ = n secⁿθ tanθ + n cosⁿθ (tanθ)
dy/dθ = n tanθ (secⁿθ + cosⁿθ ) -----eq2
to find dy/dx : calculate dy/dθ *dθ/dx
so,
dy/dx = [n tanθ (secⁿθ + cosⁿθ )]/[ tanθ (secθ + cos θ)]
dy/dx = [n (secⁿθ + cosⁿθ )]/[ (secθ + cos θ)]
(dy/dx)² = [n^2 (secⁿθ + cosⁿθ )^2]/[ (secθ + cos θ)^2]
= [n^2 (sec^2ⁿθ + cos^2ⁿθ +2secⁿθcosⁿθ )]/[ (sec^2θ + cos ^2θ + 2secθcos θ)]
(dy/dx)²= [n^2 (sec^2ⁿθ + cos^2ⁿθ +2)]/[ (sec^2θ + cos ^2θ + 2)] -----eq3
now find
![{x}^{2} {x}^{2}](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+)
x²= (secθ - cosθ)²
x² = sec^2θ + cos^2θ -2
if now add 4 in LHS then we get sec^2θ + cos^2θ +2 in RHS
(x²+4) = sec^2θ + cos^2θ +2 ----eq4
By the same way
(y²+4) = sec^(2n)θ + cos^(2n)θ +2 ----eq5
Now place these values from eq4 and eq 5 in eq3
[ (sec^2θ + cos ^2θ + 2)](dy/dx)²= [n^2 (sec^2ⁿθ + cos^2ⁿθ +2)]
(x²+4)(dy/dx)^2 =n²(y²+4)
Hope it helps you.
Answer: (a) (x²+4)(dy/dx)²=n²(y²+4)
Solution:
x= secθ-cosθ
dx/dθ = secθ tanθ - (-sin θ)
dx/dθ = secθ tanθ +sin θ
dx/dθ = tanθ (secθ + cos θ) ---eq1
same way differentiate y =secⁿθ-cosⁿθ
dy/dθ = n sec(ⁿ-1)θ secθ tanθ - n cos(ⁿ-1)θ(-sinθ)
dy/dθ = n secⁿθ tanθ + n cosⁿθ (tanθ)
dy/dθ = n tanθ (secⁿθ + cosⁿθ ) -----eq2
to find dy/dx : calculate dy/dθ *dθ/dx
so,
dy/dx = [n tanθ (secⁿθ + cosⁿθ )]/[ tanθ (secθ + cos θ)]
dy/dx = [n (secⁿθ + cosⁿθ )]/[ (secθ + cos θ)]
(dy/dx)² = [n^2 (secⁿθ + cosⁿθ )^2]/[ (secθ + cos θ)^2]
= [n^2 (sec^2ⁿθ + cos^2ⁿθ +2secⁿθcosⁿθ )]/[ (sec^2θ + cos ^2θ + 2secθcos θ)]
(dy/dx)²= [n^2 (sec^2ⁿθ + cos^2ⁿθ +2)]/[ (sec^2θ + cos ^2θ + 2)] -----eq3
now find
x²= (secθ - cosθ)²
x² = sec^2θ + cos^2θ -2
if now add 4 in LHS then we get sec^2θ + cos^2θ +2 in RHS
(x²+4) = sec^2θ + cos^2θ +2 ----eq4
By the same way
(y²+4) = sec^(2n)θ + cos^(2n)θ +2 ----eq5
Now place these values from eq4 and eq 5 in eq3
[ (sec^2θ + cos ^2θ + 2)](dy/dx)²= [n^2 (sec^2ⁿθ + cos^2ⁿθ +2)]
(x²+4)(dy/dx)^2 =n²(y²+4)
Hope it helps you.
Similar questions